1 - The Brain Drain in Africa: An Emerging Challenge to Health Professionals’ Education: Delanyo Dovlo - Delanyo Dovlo (Journal of Higher Education in Africa, 2004)
A health crisis is facing sub-Saharan Africa. The population has increased mark- edly. In recent decades, communicable diseases and ‘new’ noncommunicable dis- ease epidemics have intensified. HIV/AIDS is perhaps the biggest health chal- lenge. However, the supply of health workers remains low and has been worsened by their migration to developed countries. This paper reviews health professionals’ ‘brain drain’ using data from Ghana and other African countries, with proxy data supplying some information on which direct data do not exist. Not only is retention of health professionals a serious challenge, but training output has also remained limited. There are few studies of how stakeholders, including institutions of ter- tiary education, can moderate the effects of brain drain. Sub-Saharan Africa cannot compete economically with industrialised countries in the same health labour mar- ket. This paper discusses ways in which educational systems and the health sector can collaborate to mitigate the effects of health professionals’ migration and to sustain health services including (a) new modes of selecting candidates for the professions, (b) establishing new and relevant curricula, (c) profiling new cadres that are better retained, and (d) co-ordinating with the health sector on bonding and community service schemes to facilitate retention.